PELANGGARAN TERHADAP THE CODE OF LAWS OF THE UNITED STATES OF AMERICA OLEH PERWAKILAN KONSULER - Geraldi, Aldo Rico (Faculty of Law, Tanjungpura University, 2018)
This research aims to analyze the violation of the Code of Laws of the United States of America by officials of the Consulate General of India. This research uses normative legal research by gathering secondary data. Data collected is using the methods of literary study by collecting legal material and information in the form of legal materials of primary sources, secondary sources, and tertiary sources. In order to get a clear explanation, the data will arrange systematically and analyzed with descriptive methods. These results of this study indicate that the act of fraud and misappropriation of visas by Devyani Khobragade has violated the United State Code, Title 18-Crimes and Criminal Procedure, Part I-Crimes, Chapter 75-Passports and Visas, § 1546. Furthermore, regarding the act of forgery of documents that have been done by Devyani, it is a violation of the United State Code against Title 18-Crimes and Criminal Procedure, Part I-Crimes, Chapter 47-Fraud and False Statements, § 1001. The action performed by Devyani Khobragade if associated with human trafficking, has also violated the provisions of 22 United State Code § 7101-Purposes and findings.